Pakistan in a changing strategic context - Behera, Ajay Darshan; Joseph C., Mathew, 1966-; University of Jammu. Centre for Strategic and Regional Studies (New Delhi : Knowledge World, 2004)
On post-1988 foreign policy of Pakistan; papers presented at two seminars organized by Centre for Strategic and Regional Studies at University of Jammu
Includes bibliographical references and index
Keywords: Pakistan -- Foreign relations -- Congresses; Pakistan -- Politics and government -- 1988- -- Congresses